Linguist, Lecturer, and Students’ Perspective on the Approach and Methodology of the Listening Textbook - Perdani, Yella Dezas (Lingua Cultura, 2024)
The research investigated the linguists, lecturers, and students' perspectives on the approach and methodology in the listening textbook. In this research, a combination of qualitative and quantitative research approaches was utilized as the research methodology. It focused on an evaluation research design that involved systematically collecting and analyzing data related to the quality of the Listening course textbook with specific emphasis on the approach and methodology. For the source of the data, the research was conducted with the participation of nine individuals: two linguists, one lecturer in the Listening course, three students who have used the textbook, and three students who have not. Data collection techniques employed were evaluation forms, which consisted of 18 statements. The findings demonstrated three main findings related to approach and methodology. They were that the aims and objectives of the textbook were in line with the course's objective, the textbook has a positive influence on the students' ability to listen, and the materials contained within the textbook were suitable for the student's level of ability.